The concepts and theories of modern democracy [ - Birch, Anthony Harold (Routledge, 2007)
Covers the analyses of the use, abuse and ambiguity of many essential concepts used in political discourse and political studies. These include basic concepts such as liberty, democracy, rights, representation, authority and political power. This text is intended for foundation courses at first or second year level